An evolutionary algorithm for path synthesis of mechanisms. - Cabrera-Carrillo, Juan Antonio; Ortiz-Fernández, Antonio; Nadal-Martínez, Fernando; Castillo-Aguilar, Juan Jesús (Elsevier, 2011)
An algorithm for synthesis of mechanisms is described in this work. The algorithm is called MUMSA (Malaga University Mechanism Synthesis Algorithm). This algorithm is an improvement of the one that was published in 2002. To check the performance of the algorithm, a comparative study of different strategies for six examples revealed in the bibliography for synthesis of four-bar and six-bar mechanisms is done. To that end, we have obtained the error between the desired and the target coupler curve in a four-bar mechanism and in a six-bar mechanism, showing that the found solutions by the MUMSA algorithm were accurate and valid for all cases.
https://openpolicyfinder.jisc.ac.uk/id/publication/16599
Keywords: Algoritmos genéticos; Optimización combinatoria; Computación evolutiva; Mechanism synthesis; Genetic algorithms; Optimization; Differential Evolution